Accidents in Chemical & Process Industries of Bangladesh: Awareness Among People Working in Chemical & Process Plants (Journal of Engineering Science, 2023)
Chemical usage has steadily expanded in tandem with economic expansion, resulting in an increase in chemical accidents. Chemical incidents endanger lives and can cause a slew of health issues for those who live near chemical factories. The purpose of this study was to evaluate the knowledge of chemical accidents in chemical sector and awareness about the risk they pose among those working in chemical facilities and process plants. The research was conducted through survey which was composed of questionnaire regarding chemical safety and chemical accident in different chemical sectors participated by 120 people working in different chemical plants. Although the process safety has not mentioned in any kind of safety rules and regulations or acts the employee should have received the safety training to mitigate hazardous situation. The study shows that there was a lack of awareness and negligence of using PPE in most of the employees. A large number of respondents were doubtful of their plants following safety rules and regulations and also there was a negligence of following rules and regulations among the employees. Though there is eagerness to take safety training but most of the plants didn’t provide proper training to their employees.Journal of Engineering Science 14(1), 2023, 53-63